Clinical presentation and evaluation of dermatomyositis - Umaima Marvi; Lorinda Chung; David F Fiorentino (Wolters Kluwer Medknow Publications, 2012)
Dermatomyositis (DM) is a chronic inflammatory disorder of the skin and muscles. Evidence supports that DM is an immune-mediated disease and 50-70% of patients have circulating myositis-specific auto-antibodies. Gene expression microarrays have demonstrated upregulation of interferon signaling in the muscle, blood, and skin of DM patients. Patients with classic DM typically present with symmetric, proximal muscle weakness, and skin lesions that demonstrate interface dermatitis on histopathology. Evaluation for muscle inflammation can include muscle enzymes, electromyogram, magnetic resonance imaging, and/or muscle biopsy. Classic skin manifestations of DM include the heliotrope rash, Gottron's papules, Gottron's sign, the V-sign, and shawl sign. Additional cutaneous lesions frequently observed in DM patients include periungual telangiectasias, cuticular overgrowth, "mechanic's hands", palmar papules overlying joint creases, poikiloderma, and calcinosis. Clinically amyopathic DM is a term used to describe patients who have classic cutaneous manifestations for more than 6 months, but no muscle weakness or elevation in muscle enzymes. Interstitial lung disease can affect 35-40% of patients with inflammatory myopathies and is often associated with the presence of an antisynthetase antibody. Other clinical manifestations that can occur in patients with DM include dysphagia, dysphonia, myalgias, Raynaud phenomenon, fevers, weight loss, fatigue, and a nonerosive inflammatory polyarthritis. Patients with DM have a three to eight times increased risk for developing an associated malignancy compared with the general population, and therefore all patients with DM should be evaluated at the time of diagnosis for the presence of an associated malignancy. This review summarizes the immunopathogenesis, clinical manifestations, and evaluation of patients with DM.